Fencing Pasture Streams, Ponds, and Wetlands - William M. Giuliano (EDIS)
WEC-210, a 3-page illustrated fact sheet by William M. Giuliano, encourages the fencing of riparian zones to exclude grazing livestock and provide better habitat for wildlife. It describes the benefits to landowners of several fencing programs of federal, state, and private organizations. Published by the UF Department of Wildlife Ecology and Conservation, May 2006.